Optical modulation of excitation-contraction coupling in human-induced pluripotent stem cell-derived cardiomyocytes - Vito Vurro; Beatrice Federici; Carlotta Ronchi; Chiara Florindi; Valentina Sesti; Silvia Crasto; Claudia Maniezzi; Camilla Galli; Maria Rosa Antognazza; Chiara Bertarelli; Elisa Di Pasquale; Guglielmo Lanzani; et al. (iScience, 2023)
Summary: Non-genetic photostimulation is a novel and rapidly growing multidisciplinary field that aims to induce light-sensitivity in living systems by exploiting exogeneous phototransducers. Here, we propose an intramembrane photoswitch, based on an azobenzene derivative (Ziapin2), for optical pacing of human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs). The light-mediated stimulation process has been studied by applying several techniques to detect the effect on the cell properties. In particular, we recorded changes in membrane capacitance, in membrane potential (Vm), and modulation of intracellular Ca2+ dynamics. Finally, cell contractility was analyzed using a custom MATLAB algorithm. Photostimulation of intramembrane Ziapin2 causes a transient Vm hyperpolarization followed by a delayed depolarization and action potential firing. The observed initial electrical modulation nicely correlates with changes in Ca2+ dynamics and contraction rate. This work represents the proof of principle that Ziapin2 can modulate electrical activity and contractility in hiPSC-CMs, opening up a future development in cardiac physiology.